Ultra scale-down approaches to enhance the creation of bioprocesses at scale: impacts of process shear stress and early recovery stages. (November 2016) - Rayat, Andrea CME; Chatel, Alex; Hoare, Mike; Lye, Gary J
Highlights: New mL-scale USD tools can predict manufacture at scale of biological material. These USD tools give new understanding of the impacts of the process environment. Tools enable bioprocess interaction studies; better understood early in development. Applications of these USD tools will help speed new therapies to manufacture. Abstract : The sensitivity of biological materials to shear stress conditions encountered during large-scale bioprocessing makes successful scale up from the bench challenging. Ultra scale-down technologies seek to use just millilitre quantities to enhance our understanding of the impact of the process environment as a basis for process optimisation. They can help speed translation of new biological discoveries to market and reduce risks encountered in scale up. They are important both as process discovery tools and as preparative tools to yield material for study of subsequent stages. In this review the focus is on the early recovery stages post fermentation or cell culture and in particular the use of continuous-flow and dead-end centrifugation integrated with preparative stages (e.g. flocculation) and subsequent depth filtration. Examples range from therapeutic antibodies, to rationally engineered (synthetic biology) host strains, to stem cells for therapy.